2018
DOI: 10.21608/mjcu.2018.56755
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Predictors of Refractory Childhood Epilepsy: Case Control Study

Abstract: Background: Each year, 3.5 million new cases of epilepsy are reported. Unfortunately, 6-14% of these children will develop refractory epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Ayca and colleagues [ 11 ] also found that abnormal neurological examination was 58 times more in drug-resistant epilepsy and was the most important risk factor, possibly reflecting the severity of brain damage. The presence of abnormal neurological examination agrees with other studies [ 10 , 17 ]. Drug-resistant epilepsy has been linked to a history of psychiatric comorbidity, particularly depression, according to Hitiris and colleagues [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Ayca and colleagues [ 11 ] also found that abnormal neurological examination was 58 times more in drug-resistant epilepsy and was the most important risk factor, possibly reflecting the severity of brain damage. The presence of abnormal neurological examination agrees with other studies [ 10 , 17 ]. Drug-resistant epilepsy has been linked to a history of psychiatric comorbidity, particularly depression, according to Hitiris and colleagues [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with Ayca and colleagues [ 11 ], who showed that a positive family history of seizures did not seem to be a risk factor for drug-resistant epilepsy. Other studies found no significant correlation between a family history of seizures and drug-resistant epilepsy [ 10 , 12 , 13 ]. Twin studies suggested that genes and, therefore, family history may have a role in the pathophysiology of epilepsy but not in its prognosis [ 14 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recurrent fits are demonstrated to be accompanied by neuronal loss especially in the hippocampal area, that could ultimately ends in recurrent excitatory circuits [8] . Likewise, El-Deen et al [9] displayed that past history of febrile seizures were significantly increased among cases with DRE than those with responsive epilepsy. In contrast, Ohtsuka et al [10] recorded no correlation between febrile seizures and DRE.…”
Section: Discussionmentioning
confidence: 96%
“…In regard to seizure frequency, the current study demonstrated higher frequency of seizures per weeks before start of treatment (p=0.03). Likewise, El-Deen et al [9] recorded that high initial seizure frequency was a significant predisposing factor of DRE.…”
Section: Discussionmentioning
confidence: 97%